Huge mesenteric low-grade fibromyxoid sarcoma: A case report and review of the literature. (21st May 2018) - Geramizadeh, Bita; Zare, Zahra; Dehghanian, Amir Reza; Bolandparvaz, Shahram; Marzban, Mahsa
Low-grade fibromyxoid sarcoma is a rare soft tissue tumor which has been mostly reported in lower extremities; however, it can also occur in other parts of the body such as head and neck and abdominal wall, but its occurrence in the abdominal cavity and mesentery of bowel is an extremely rare event and has very rarely been reported. Herein, we report our experience with a 24-year-old lady with a huge mesenteric mass, turned out to be low-grade fibromyxoid sarcoma. This case is the largest one reported in the English literature. We will also discuss about the previously reported cases of low-grade fibromyxoid sarcoma in the English literature.